![image](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7B36%7D%29%5E%7B-x%7D%3D++%5Csqrt%7B+%5Cfrac%7B1%7D%7B6%7D+%7D%5C%5C6%5E%7B-2x%7D%3D6%5E%7B-0%2C5%7D%5C%5C-2x%3D-0%2C5%7C%3A%28-2%29%5C%5Cx%3D0%2C25%5C%5C%5C%5C%5C%5C3%2A5%5E%7B2x-1%7D-2%2A5%5Ex%3D5%5C%5C3%2A5%5E%7B-1%7D%2A5%5E%7B2x%7D-2%2A5%5Ex-5%3D0%5C%5C0%2C6%2A5%5E%7B2x%7D-2%2A5%5Ex-5%3D0%5C%5Ct%3D5%5Ex%5C%5C0%2C6t%5E2-2t-5%3D0%7C%2A5%5C%5C3t%5E2-10t-25%3D0%5C%5CD%3D%28-10%29%5E2-4%2A3%2A%28-25%29%3D100%2B300%3D400%3D20%5E2%5C%5Ct_1%3D%2810%2B20%29%2F6%3D5%5C%5Ct_2%3D%2810-20%29%2F6%3D-10%2F6%3D-5%2F3%5C%5C%5C%5C+5%5Ex%3D5%5C%5C5%5Ex%3D5%5E1%5C%5Cx%3D1%5C%5C%5C%5C5%5Ex%3E0%5C%5C5%5Ex+%5Cneq+-5%2F3%5C%5C%5C%5Cx%3D1+)
0\\5^x \neq -5/3\\\\x=1 " alt="(\frac{1}{36})^{-x}= \sqrt{ \frac{1}{6} }\\6^{-2x}=6^{-0,5}\\-2x=-0,5|:(-2)\\x=0,25\\\\\\3*5^{2x-1}-2*5^x=5\\3*5^{-1}*5^{2x}-2*5^x-5=0\\0,6*5^{2x}-2*5^x-5=0\\t=5^x\\0,6t^2-2t-5=0|*5\\3t^2-10t-25=0\\D=(-10)^2-4*3*(-25)=100+300=400=20^2\\t_1=(10+20)/6=5\\t_2=(10-20)/6=-10/6=-5/3\\\\ 5^x=5\\5^x=5^1\\x=1\\\\5^x>0\\5^x \neq -5/3\\\\x=1 " align="absmiddle" class="latex-formula">